KEBIJAKAN HUTANG, UKURAN PERUSAHAAN, KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BEI - Diana Uffiah; Ana Kadarningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
This study aimed to examine the effect of debt policy, firm size and investment decision on the firm value of coal mining companies which were listed on Indonesia Stock Exchange for the period of 2013-2018. The population was 26 coal mining companies. While, the sampling collection technique used purposive sampling in which there were 20 companies as sample. Analysis method which used in this study are multiple regression analysis, classic assumption test, determinant coefficient, f-test, and t-test. The result of the study shows that firm size and debt policy had negative but no significant effect on firm value, the greater the company debt, the higher the risk and costs would be, moreover, it affected the investors perceptions of investing. While investment decision had positive and significant effect on the firm value. As consequence, the investment increase made positive prospects in the future in which it increased the firm value.